Model Kesetimbangan Adsorpsi Logam Tembaga (Cu (II)) Menggunakan Cangkang Kepiting Sebagai Adsorben - Reny Nur Hidayah; Drastinawati Drastinawati; Silvia Reni Yenti (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Copper metal pollution (Cu (II)) in the water has a negative impact on people's lives. One effort to reduce the copper metal content is by the adsorption process. The purpose of this study was todetermine the effect of adsorption temperature (30, 40, 50 ° C) and adsorbate concentration (2, 3, 4 mg / L) and to test the adsorption isotherm equilibrium model on the adsorption Cu (II) bycrab shell by model equation approach Langmuir and Freundlich. The results showed if the adsorption temperature rise, the adsorbent adsorption capacity of crab shells (qe) is decreasedand if the concentration is decreased, the adsorbent adsorption capacity of crab shells (qe) is increased. The highest absorption rate was obtained at 30 ° C with a concentration of 4 mg / Lof adsorbate at 1.558 mg / g. The copper metal adsorption mechanism (Cu (II)) by the crab shellhas a match with the Freundlich isoterm model which represents the physical and adsorption Freundlich isoterm model which represents the chemical adsorption.Keywords: Adsorption, Crab Shell, Equilibrium Model, Copper (II)